1988
DOI: 10.3354/meps044065
|View full text |Cite
|
Sign up to set email alerts
|

The micronucleus test: examples of application to marine ecology

Abstract: Marine mussels Mytdus galloprovincialis were examined from stations in the Venice Lagoon and La Spezia Roads (Italy) characterized by different degrees of pollution. Frequencies of micronuclei detected in gill tissue are suggested as a technique for rapid, easy and sensitive monitoring of environmental genotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
8

Year Published

1992
1992
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 3 publications
(3 reference statements)
1
22
0
8
Order By: Relevance
“…This idea is based on the assumption that nuclear abnormalities induce functional disorders with a consequent expression on the cell membrane, allowing their identification by the spleen and consequent catabolism. Previously, other authors (Das and Nanda, 1986;Brunetti et al, 1988) suggested a dose-related cytotoxicity, which killed the erythrocytes instead of forming a nonlethal nuclear lesion, explain the impairment in expression of nuclear abnormalities. Therefore, to explain the simultaneous occurrence of splenic hemosiderosis and disturbances in ENA expression, the conjugation of both mechanisms should also be accepted, namely, in the presence of xenobiotics with hemolytic and genotoxic properties.…”
Section: Interaction Of Biomarkersmentioning
confidence: 96%
“…This idea is based on the assumption that nuclear abnormalities induce functional disorders with a consequent expression on the cell membrane, allowing their identification by the spleen and consequent catabolism. Previously, other authors (Das and Nanda, 1986;Brunetti et al, 1988) suggested a dose-related cytotoxicity, which killed the erythrocytes instead of forming a nonlethal nuclear lesion, explain the impairment in expression of nuclear abnormalities. Therefore, to explain the simultaneous occurrence of splenic hemosiderosis and disturbances in ENA expression, the conjugation of both mechanisms should also be accepted, namely, in the presence of xenobiotics with hemolytic and genotoxic properties.…”
Section: Interaction Of Biomarkersmentioning
confidence: 96%
“…were very low, while in autumn of the next year they were 3-10 times higher. Though baseline frequency of MN depends on variety of biotic and abiotic factors (Brunetti et al, 1988), it can be assumed that higher water temperature in the offshore areas of the Baltic and the North Sea affects mitotic activity and MN formation in fish. Micronuclei are formed during cell division, and the mitotic activity of poikilotherm organisms very largely depends on water temperature (Brunetti et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Although originally developed for use with mice (Schmid, 1976), the EMN technique was subsequently modi"ed for laboratory application in "sh (Hooftman and de Raat, 1982). This modi"-cation, known as the &&piscine micronucleus test'' has been proposed as a biological indicator of chemical contamination in "sh (Das and Nanda, 1986;Metcalfe, 1988;Carrasco et al, 1990;Pacheco and Santos, 1997a,b), amphibians Jaylet et al, 1986;Zoll-Moreux and Ferrier, 1999), and invertebrates (Brunetti et al, 1988;Scarpato et al, 1990;Venier et al, 1997).…”
Section: Introductionmentioning
confidence: 99%